Kardiochirurgia dorosłychPostoperative, early and late pulmonary functions – off-pump vs. on-pump coronary artery bypass surgery - Rachwalik, Maciej; Pelczar, Marek; Goździk, Anna (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2007)
In order to assess changes in respiratory system efficiency after performing different types of surgical heart muscle revascularization, various respiratory parameters were analyzed. The research was carried out on two groups of patients operated on in the Cardiac Surgery Clinic of the Medical University in Wrocław. Patients with low ejection fraction and physician-diagnosed chronic respiratory disease were excluded from the research. The OPCAB group consisted of 26 patients operated on without cardiopulmonary bypass (CPB). The CABG group consisted of 30 patients in whom revascularization with CPB was performed. At the early (on the 5th day) and late (after 2.5 and 6 months) postoperative examination spirometric tests were performed and their results were assessed. In both groups of patients restrictive disturbances of ventilation were observed. The early postoperative examination, performed on the 5th day, revealed reduction of parameters FEV1 to 51.5% in the OPCAB group and 49% in the CABG group and VC parameters 51.2% and 51%, respectively. The first late postoperative examination (2.5 months after surgery) showed a gradual increase of each FEV1 parameter in the OPCAB group up to 78.5% and in the CABG group up to 73.8%. VC increased to 72.0% in the OPCAB group and to 73.1% in the CABG group. In the last examination (6 months after surgery) insignificant restrictive disturbances were observed, expressed by the following parameters: FEV1 81.4% OPCAB group and 89.0% CABG, and VC 78.2% and 85.6% respectively. Conclusion: Operations performed through the median sternotomy generate restrictive disturbances of ventilation, which tend to subside with time. It has not been proved that cardiopulmonary bypass has an impact on postoperative deterioration of respiratory efficiency. At the same time a linear improvement of respiratory efficiency has been indicated. After six months the results of spirometric tests were similar to the preoperative values.